Legal status of chemical fingerprints under section 45 of Malaysia's evidence act 1950 - Mohamad Pauzi, Jinan; Ariffin, Mariani (Elsevier, 2015)
Effective enforcement of environmental legislation is the key to ensure successful environmental protection and pollution control. For cases brought under the Environmental Quality Act 1974, the decision of criminal case tried is derived from the application of the law of evidence, specifically the Evidence Act 1950. In environmental forensics, chemical fingerprinting is one of the tools used to help identify sources of pollution and may form a defensible piece of evidence for prosecutors. The objective of this paper is to examine the position of chemical fingerprint evidence under Section 45 of the Evidence Act 1950. This research can provide an introductory guideline that can be of use to environmental law enforcers, forensic experts and other relevant stakeholders